Sweden : Financial Sector Assessment Program Update: Technical Note on Household Indebtedness: Implications for Financial Stability. (IMF Staff Country Reports; Country Report ;, 2011)
As in other advanced economies, there has been a significant run-up of household debt in Sweden during the last two decades accompanied by rising housing prices, prompting concerns about sustainability and the implications for financial stability. The rise in household debt and the banking system's increased exposure to mortgage debt resulted with the changes in the macroeconomic environment. The note explores implications for financial stability of household indebtedness as well as Sweden's specific institutional features to ensure resilience of the financial system.